Europe today a twenty-first century introduction - Tiersky, Ronald 1944-.; Jones, Erik.; Genugten, Saskia van. (Lanham, Md. Rowman & Littlefield Publishers, 2011)
This book, a true twenty-first-century enterprise, offers a sustained and unified set of both country case studies and analysis of the European Union. The contributors, an authoritative group of Americans and Europeans, explore the new Europe, West and East, using intertwining themes of domestic politics, European integration, and European security. Each chapter provides a foundation of basic political information and explanation, enhanced by distinctive and informed perspectives on current issues. It presents an up-to-date treatment of the war in Iraq, debates over NATO's evolving role, U.S.-European relations, enlargement issues, and the challenges of terrorism in a European context. With its strong international emphasis and focus on Europe before and after Iraq, this book leads readers toward a coherent view of intra-European conflicts, Europe and the United States, and Europe's international responsibilities. A new website devoted exclusively to the book, with regularly updated statistics, analysis, and links for each chapter, provides a resource for those seeking additional information.
Timeline of events leading to the current state of the European Union. The European outlook / Ronald Tiersky, Saskia van Genugten, and Erik Jones -- Country Studies. France: the Sarkozy presidency in historical perspective / Gabriel Goodliffe -- Great Britain: from New Labour to new politics? / Jonathan Hopkin -- Germany: two decades of passage from Bonn to Berlin / Helga A. Welsh -- Italy: politics in the age of Berlusconi / Gianfranco Baldini -- Scandinavia: still the middle way? / Eric S. Einhorn and John Logue -- Russia: European or not? / Bruce Parrott -- Poland 20 years later: the long arm of transition / Ben Stanley -- Thematic Chapters. European integration: progress and uncertainty / John Van Oudenaren -- Economic governance and varieties of capitalism / Benedicta Marzinotto -- Europe and the global economic crisis / Erik Jones -- European law and politics / R. Daniel Kelemen -- Migration in Europe / Jonathan W. Moses -- Still at the crossroads: Europe, the United States, and NATO / Simon Duke and Roberta Haar.
Includes bibliographical references and index.
Keywords: European Union countries -- Politics and government -- 21st century; Europe -- Politics and government -- 21st century; Europe -- Forecasting